2003
DOI: 10.1163/156856103770572025
|View full text |Cite
|
Sign up to set email alerts
|

Physico-mechanical properties of particleboards bonded with pine and wattle tannin-based adhesives

Abstract: This study investigated the physical and mechanical properties of particleboards made using two types of tannin-based adhesives, wattle and pine, with three hardeners, paraformaldehyde, hexamethylenetetramine(hexamine) and TN (tris(hydroxyl)nitromethane), by measuring the physical (thickness swelling, linear expansion and water absorption) and mechanical properties (bending strength and internal bond strength). The performance of the particleboards made using tannin-based adhesives was in uenced by physical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 13 publications
(16 reference statements)
1
8
0
1
Order By: Relevance
“…It was shown that, for the bark boards, a higher resin content (>10%) was necessary to reach this benchmark. This is consistent with the findings of Kim et al [ 40 ]. Higher density results in higher TS, as is known from the literature [ 41 ], but this could not be confirmed in the present study, probably due to low compression.…”
Section: Resultssupporting
confidence: 94%
“…It was shown that, for the bark boards, a higher resin content (>10%) was necessary to reach this benchmark. This is consistent with the findings of Kim et al [ 40 ]. Higher density results in higher TS, as is known from the literature [ 41 ], but this could not be confirmed in the present study, probably due to low compression.…”
Section: Resultssupporting
confidence: 94%
“…This statement does not work in all cases of tannin-based adhesives. Kim et al [59] investigated the physical and mechanical properties of particleboard made using two types of tannin-based adhesives, wattle and pine, with three hardeners. The bending strength of the particleboard made using the wattle tannin-based adhesive with all three hardeners increased slightly, while in case of the pine tannin-based particleboard, a decrease in bending strength was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Os taninos condensados constituem mais de 95% da produção mundial de taninos comerciais ultrapassando a marca de 350.000 t/ano (GUANGCHENG et al, 1991). Kim et al (2003) avaliaram as propriedades físicas e mecânicas de chapas aglomeradas confeccionadas com tanino obtido de pinus e acácia negra. Os resultados foram satisfatórios, sendo afirmado pelos autores que a temperatura da prensa e o tempo de prensagem são fatores limitantes na utilização dos tipos de adesivos naturais aplicados para as propriedades avaliadas.…”
Section: Introductionunclassified